The evaluation of the remained term in the limit theorem for the functions of the elements of the continued fraction - Misevičius, G. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. А. Мисявичус. Оценка остаточных членов в предельных теоремах для распределения функций от элементов цепных дробейG. Misevičius. Liekamojo nario įvertinimas ribinėse teoremose apie grandininių trupmenų parametrų pasiskirstymo konvergenciją